Learn Kotlin Programming : a Comprehensive Guide to OOP, Functions, Concurrency, and Coroutines in Kotlin 1. 3, 2nd Edition. - Samuel, Stephen (Packt Publishing, Limited, 2019)
The aim of the book is to teach you the fundamentals of the Kotlin language. This book will be an update based on the latest major version of Kotlin 1.3. This book provides a detailed introduction to Kotlin that shows you all its features and will enable you to write Kotlin code to production.